2009
DOI: 10.1152/ajpheart.00230.2009
|View full text |Cite
|
Sign up to set email alerts
|

eNOS uncoupling and endothelial dysfunction in aged vessels

Abstract: Endothelial nitric oxide synthase (eNOS) uncoupling is a mechanism that leads to endothelial dysfunction. Previously, we reported that shear stress-induced release of nitric oxide in vessels of aged rats was significantly reduced and was accompanied by increased production of superoxide (18,27). In the present study, we investigated the influence of aging on eNOS uncoupling. Mesenteric arteries were isolated from young (3 mo) and aged (24 mo) C57 BL/6J mice. The expression of eNOS protein in young vs. aged mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
260
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 313 publications
(277 citation statements)
references
References 34 publications
11
260
3
3
Order By: Relevance
“…Reduced cofactor availability for eNOS can decrease NO production 19. Previous reports show that OVX significantly lowers plasma NO metabolite [NO x; plasma nitrate+nitrite] levels in rats 55.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced cofactor availability for eNOS can decrease NO production 19. Previous reports show that OVX significantly lowers plasma NO metabolite [NO x; plasma nitrate+nitrite] levels in rats 55.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with decreased endothelial NOS‐dependent NO synthesis and endothelium‐dependent vasodilation, suggesting a possible role for dietary nitrates to support NO production in age‐related conditions like osteoporosis. 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, senescent human aortic ECs (HAECs) exhibited higher ICAM-1 expression and lower eNOS activity [168]. Accordingly, the eNOS protein isolated from mesenteric arteries in young mice has the dimer configuration, whereas eNOS protein from aged mice was mostly uncoupled to monomers [169]. The same study revealed that eNOS uncoupling contributed to increased superoxide levels in aged vessels and was due to a reduced BH 4 availability [169].…”
Section: The Roles Of H 2 S and No In Agingmentioning
confidence: 94%
“…Accordingly, the eNOS protein isolated from mesenteric arteries in young mice has the dimer configuration, whereas eNOS protein from aged mice was mostly uncoupled to monomers [169]. The same study revealed that eNOS uncoupling contributed to increased superoxide levels in aged vessels and was due to a reduced BH 4 availability [169]. The aging-related EC dysfunction is largely ascribed to oxidative stress and inflammation [170,171].…”
Section: The Roles Of H 2 S and No In Agingmentioning
confidence: 97%
“…Superoxide production in mesenteric arteries was assessed by using dihydroethidium (DHE) and an HPLC/fluorescence detector-based assay to detect 2-hydroxyethidium (2-EOH), a superoxide-induced oxidative product of DHE (15,55). Isolated mesenteric arteries were incubated in control media and in the presence of 0.3 and 1 mmol/l Met, and Met (1 mmol/l) plus enalapril (100 mol/l, ACE inhibitor), losartan (10 M), or 3-benzyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo(4,5-d)pyrimidine (VAS2870, 5 M, a selective inhibitor of NADPH oxidase; Enzo Life Sciences) for 24 h, respectively.…”
Section: Animals and Vesselsmentioning
confidence: 99%